Survei Keterampilan Teknik Dasar Siswa Sekolah Sepakbola Iguana Kicker’s Club Usia 14 Tahun di Kota Batu - Syahdilla, Ryan Reykhan; Amiq, Fahrial (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
This study aims to identify and analyze the level of basic soccer technique skills in SSB IKC Kota Batu players aged 14 years. The Survey method is the choice in using this research with quantitative descriptive analysis. A total of 28 students of the Iguana Kicker's Club soccer school with a speculation age of 14 years became the subjects in this study. The test instruments used in this study include basic skills in playing soccer, namely: (a) passing and stopping tests, (b) heading tests, (c) dribbling tests, (d) shooting tests. Data collection using test form measurement techniques with observation methods through the stages, namely: planning, implementation, and reporting of research results. Data analysis in this study used descriptive percentage statistics. The results of the basic soccer skill test given to 28 students showed that overall the students' basic soccer technique skills were in the sufficient category. Thus, this study is expected to help coaches in evaluating students who show less than optimal skills on several of these basic technique test instruments.